An observational audit of pain scores post orthopaedic surgery at a level two state hospital in Cape Town - Hauser, Neil David (Department of Anaesthesia, 2016)
An audit cycle of post-operative pain scores and patient satisfaction of pain control in orthopaedic patients at a Level Two State Hospital in Cape Town. In addition as part of the information collected during the research process we will audit the following: Intraoperative anaesthetic techniques, post-operative analgesia consumption and analgesic methods as well as any side effects to analgesic medication used in orthopaedic patients peri-operatively at Victoria Hospital Wynberg (VHW) will also be noted. Postoperative pain control is an essential, yet often inadequately managed part of peri-operative patient care. Adequate analgesia is important not only for patient comfort but also for maintaining stable physiology, facilitating recovery from surgery, enabling rehabilitation and to potentially decrease length of hospital stay post-operatively. International audits have previously shown that pain is poorly managed post-operatively in surgical patients. At facilities in the Western Cape, pilot student audits have shown that management of post-operative pain is also potentially inadequate. This means that surgical patients potentially experience severe pain in the first 48 hours following surgery, increasing the risk of chronic pain development as well as post-operative complications thereby placing a greater burden on already limited health care resources. These proposed observational audits will look at a population of orthopaedic patients at a Level Two Hospital in Cape Town. The study will be performed at Victoria Hospital Wynberg (VHW). VHW performs a large number of orthopaedic cases each week, giving us access to a potentially large number of patients. The choice of orthopaedic patients is due to the fact that orthopaedic surgery has been shown in some studies to be associated with a greater degree of post-operative pain as rated by patients when compared to other surgical disciplines. The high levels of pain associated with orthopaedic surgery are thought to be due to the degree of tissue trauma and the nature of tissue involved in the surgery itself.